Nonlinear impact of unconventional water use on water resource sustainability in China: A perspective on water poverty - Ruifang Wang; Fengping Wu; Yingwen Ji; Chen Feng (Ecological Indicators, 2024)
Unconventional water serves as a bridge to water sustainability. However, many developing nations still have a long way to go in terms of unconventional water utilization. Different regional characteristics lead to different consumption capacities for unconventional water. Consequently, more unconventional water use (UWU) may not necessarily be positive for alleviating water poverty. However, there is a significant research gap in this field. This paper aims to answer three key questions: “Whether UWU consistently alleviates water poverty?” “Is this effect spatially heterogeneous?” and “What role do economic factors play in addressing water poverty?” For that, this paper focused on 30 provinces in China, with the sample period spanning from 2006 to 2021. To identify the mechanisms through which UWU alleviates water poverty, this paper employed a panel fixed-effects model using the Water Poverty Index (WPI) as the dependent variable and the square of UWU amount as an independent variable. The results indicate a non-linear impact of UWU on WPI, with the significance of impact influenced by GDP per capita (PGDP). Furthermore, threshold regressions were conducted with PGDP as the threshold variable. The results revealed a double-threshold effect of PGDP in the impact of UWU on WPI, displaying “U” or inverted “U” shape as PGDP develops: When PGDP is less than or equal to RMB 13,574, UWU demonstrates a negative effect on WPI; when PGDP ranges from RMB 13,574 to RMB 53,653, the effect turns positive; however, when PGDP exceeds RMB 53,653, the effect turns back to negative. The findings confirm that more UWU is not always better. Sustainable utilization plans of water resources must be tailored to local conditions, especially considering the unique characteristics of the regional economy.